2021
DOI: 10.1111/odi.14073
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib has minimal effects on inflammatory and osteopenic phenotypes in a murine cherubism model

Abstract: Objective: Cherubism is a genetic disorder characterised by bilateral jawbone deformation. The associated jawbone lesions regress after puberty, whereas severe cases require surgical treatment. Although several drugs have been tested, fundamental treatment strategies for cherubism have not been established. The effectiveness of imatinib has recently been reported; however, its pharmaceutical mechanism remains unclear. In this study, we tested the effects of imatinib using a cherubism mouse model. Methods:We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 3 , 7 In support of these facts, a recent study showed that the efficacy of imatinib, a BCR-ABL fusion protein inhibitor, differs between human and mouse cherubism, suggesting that the key signaling mechanisms that cause human cherubism are not identical to those in mice. 41 , 42 SYK has been shown to be a promising therapeutic target for cherubism in our studies with SH3BP2 cherubism mice. 3 , 43 Given the possible differences in cherubism pathogenesis between humans and mice, it may be conceivable that SYK inhibitor treatment for human cherubism may not be as effective as for cherubism in mice.…”
Section: Discussionmentioning
confidence: 69%
“… 3 , 7 In support of these facts, a recent study showed that the efficacy of imatinib, a BCR-ABL fusion protein inhibitor, differs between human and mouse cherubism, suggesting that the key signaling mechanisms that cause human cherubism are not identical to those in mice. 41 , 42 SYK has been shown to be a promising therapeutic target for cherubism in our studies with SH3BP2 cherubism mice. 3 , 43 Given the possible differences in cherubism pathogenesis between humans and mice, it may be conceivable that SYK inhibitor treatment for human cherubism may not be as effective as for cherubism in mice.…”
Section: Discussionmentioning
confidence: 69%
“…Clinical outcomes were satisfying with imatinib, a tyrosine kinase inhibitor, as the volume of the lesions decreased ( 39 ). Interestingly, this off-study and off-label treatment efficient to decrease the volume of the patients’ lesions did not have any effect on the cherubism mouse ( 44 ). However, Yoshimoto and colleagues demonstrated that treating with a very new second-generation SYK inhibitor (Entospletinib) rescued the cherubism phenotype ( 45 ).…”
Section: Discussionmentioning
confidence: 89%
“…Quantitative polymerase chain reaction (qPCR) was performed as previously described (35, 36). Total RNA from cultured cells or spleens was extracted using RNAiso Plus (Takara Bio).…”
Section: Methodsmentioning
confidence: 99%